Strategi Komunikasi Government Relations Pemkot Dalam Usaha Branding Salatiga Sebagai Kota Gastronomi - Kurnia, Jessica Meisya; Huwae, George Nicholas (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
This study focuses on the efforts to brand Salatiga as a Gastronomy City through Government Relations) communication strategies. Salatiga, with its rich cultural and culinary heritage, has significant potential to become a gastronomy city. However, various challenges, such as a lack of coordination among stakeholders and insufficient promotion, hinder the achievement of this goal. The Salatiga City Government seeks to overcome these obstacles through programs that involve multiple parties, but issues such as inconsistent messaging and limited supporting facilities remain. This research aims to analyze the communication strategies used in branding Salatiga as a Gastronomy City and to provide recommendations for enhancing the effectiveness of Government Relations in local tourism development. The research method used is qualitative, involving interviews with the Public Relations team of the Salatiga City Government. The findings indicate that Salatiga's branding strategy is still weak and inconsistent. The Salatiga City Government is expected to maximize the city's gastronomic potential and increase public awareness of Salatiga's branding as a Gastronomy City.